Central banks should communicate their interventions in the foreign exchange market - Lukas Menkhoff; Tobias Stöhr (DIW Economic Bulletin, 2017)
Central banks frequently intervene in foreign exchange markets. Using recognized criteria this report analyzes the probability of success in a data set of 4,500 intervention episodes in 33 countries. It is important to differentiate among exchange rate regimes because each focuses on a different goal. While flexible exchange rate regimes intervene less frequently and seek to influence trends, other regimes target exchange rate stabilization by establishing a band within which the exchange rate can float. Interventions are generally more successful when they involve larger volumes, follow the exchange rate trend, and are oriented on the fundamental value. When decision makers also communicate their interventions or changes to exchange rate policies, the effects of these are likely to be stronger. Central bankers should therefore complement their interventions with communication to improve their likelihood of success.
Keywords: F31; F33; E58; 330; foreign exchange intervention; exchange rate regimes; actual interventions; communication